Prevalence of metabolic syndrome among breast cancer survivors in East Coast of Peninsular Malaysia - Mohd Razif Shahril; Syed Amirfaiz; Pei Lin Lua; Ali Nurnazahiah; Nor Syamimi Zakarai; Ving Lok Kow; Aryati Ahmad; Suhaina Sulaiman (BMC, 2021)
Abstract Background To date, limited data are available on metabolic syndrome prevalence among breast cancer survivors in Malaysia. Therefore, this study was conducted to determine the prevalence of metabolic syndrome and abnormal metabolic syndrome components among breast cancer survivors in East Coast of Peninsular Malaysia. Methods This cross-sectional study included 95 breast cancer survivors (age 53.7 ± 7.6 years) who have completed main cancer treatments for ≥6 months. Cancer survivors were recruited from two main government hospitals in Kelantan and Terengganu using a purposive sampling method. Results According to the Harmonized criteria, the metabolic syndrome prevalence was 50.5%. Among those with metabolic syndrome, the most prevalent abnormal metabolic components were triglycerides (91.2%), fasting blood glucose (79.6%) and HDL-c level (78.4%). Except for total cholesterol and LDL-c, all other metabolic syndrome components were significantly different (p < 0.05) between those with and without metabolic syndrome. Significant differences between metabolic syndrome and non-metabolic syndrome groups were found for weight, BMI, waist circumference, body fat percentage and cancer stages (p < 0.05). However, no significant relationship was reported between sociodemographic, clinical parameters and metabolic syndrome among breast cancer survivors in this study. Conclusions Metabolic syndrome was highly prevalent among breast cancer survivors. It is recommended for health care professionals to closely monitor and improve the triglycerides, blood glucose and HDL-c level of the breast cancer survivors under their care to control the detrimental effect of metabolic syndrome.